Narasi Diskriminatif Pascakonflik pada Masyarakat Kristen: 20 Tahun Pengalaman Pengungsi Kayeli di Ambon, Maluku - Christin Pattiserlihun, Selvone; Iqbal Ahnaf, Mohammad; Rif’ah Hasaniy, Nur (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
The 1999 conflict in Maluku left scars that lasted 20 years after the conflict. This phenomenon is directly reflected in the narratives of post-conflict society, which are still prevalent in daily conversations. During their 20 years of surviving in Ambon as refugees, the Kayeli community had various experiences forms (violent and peaceful ones). The struggle of the Kayeli refugees reflects the damages created by conflict in communal relations a year after the war's end. This condition has not been sufficiently discussed in studies of post-conflict society. This paper aims to describe the struggle of the refugee community as a vulnerable group of people living with narratives of violence in the post-conflict in Ambon. This paper is based on in-depth interviews with 8 informants from the Kayeli refugee community to collect the data in 2023. The results reveal that the conflict experiences depicted in this group illustrate discrimination and struggle in communal relations in new areas where they were resettled from their war-torn villages. This paper describes the refugees' responses to conflict narratives based on their Christian beliefs. This is how the refugee community continues to live their lives by coping with the discriminating narratives in their new community.